Investigating aberrant DNA methylation patterns in LOXL2 as a potential predictor of diabetes-induced cardiac dysfunction - Erasmus, Melisse (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.